Multiwalled carbon nanotube/montmorillonite hybrid filled ethylene‐co‐vinyl acetate nanocomposites with enhanced mechanical properties, thermal stability, and dielectric response. Issue 7 (27th July 2017) - Bhuyan, B.; Roy, A.; Srivastava, S. K.; Mittal, V.
Abstract : Homogeneous multiwalled carbon nanotube/montmorillonite hybrid filler (HMM) dispersion was prepared by co‐ultrasonication and was subsequently used to prepare ethylene‐co‐vinyl acetate (EVA) nanocomposites by solution blending method. XRD and TEM analysis of HMM confirm significant interaction between the montmorillonite (MMT) layers and multiwalled carbon nanotubes (MWCNT) in line with previous reports. Analysis of the nanocomposites shows the constituent fillers to be homogeneously dispersed in EVA matrix. Mechanical properties of neat EVA are remarkably improved with HMM content up to 3 wt% followed by reversion. Maximum improvement observed in tensile strength, elongation at break, and toughness are 424%, 109%, and 1122%, respectively. Results show maximum thermal stability at 4 wt% and best dielectric response at 1 wt% HMM content. Exceptional mechanical and dielectric properties of EVA nanocomposites attained may be attributed to homogeneous dispersion of fillers and improved polymer–filler interaction. Comparison shows excellent synergy between MWCNT and MMT towards mechanical reinforcement of EVA. POLYM. ENG. SCI., 58:1155–1165, 2018. © 2017 Society of Plastics Engineers